Heraclius. A Commander in the Service of Leo I and Zeno - Leszka, Mirosław J. (Studia Ceranea, 2023)
Heraclius’ career, the one that can be traced in primary sources, lasted seven years. In its course he held the position of comes rei militaris and, perhaps, magister militum vacans and magister militum per Thracias. His greatest victories came in a war against the Vandals. They forced Gaiseric, the Vandal’s leader to undertake peace negotiations. However, these victories were eclipsed by Heraclius’ failures in the fight against Theodoric Strabo’s Goths and by the shameful circumstances of his death.